Literature Study: The Effect of Butterfly Pea Flowers (Clitoria ternatea L.) on Human Health - Chylen Setiyo Rini; Sukmawati Sukmawati; Ade Teti Vani; Ony Wibriyono Angkejaya; Mustar Mustar (PT. Anagata Sembagi Education, 2025)
This study aims to evaluate and summarize the findings from studies related to the effects of butterfly pea flowers (Clitoria ternatea L.) on human health, particularly those related to their therapeutic properties, including antioxidant, anti-inflammatory, neuroprotective, and relaxing effects. The research method used in this study is Systematic Literature Review (SLR). This approach was chosen because of its ability to systematically identify, evaluate, and summarize relevant research results on butterfly pea flowers. Article searches were conducted through academic databases such as PubMed, ScienceDirect, and Google Scholar, focusing on studies that discuss the effects of butterfly pea flowers on human health. Based on the analysis results of various existing studies, butterfly pea flowers show great potential in supporting human health. The content of bioactive compounds, such as flavonoids, anthocyanins, and alkaloids, provides various significant therapeutic benefits. Flavonoids and anthocyanins have strong antioxidant properties, play a role in fighting free radicals, and preventing oxidative damage that can cause degenerative diseases. In addition, these compounds have anti-inflammatory effects that are beneficial in managing inflammatory conditions such as arthritis, asthma, and heart disease. Butterfly pea flowers also show neuroprotective effects that can protect nerve cells, improve cognitive function, and protect the brain from neurodegenerative diseases such as Alzheimer's and Parkinson's. Alkaloids in butterfly pea flowers also have a relaxing effect that can help reduce anxiety and stress, and improve mental well-being. Although the results obtained are very promising, most studies are still limited to laboratory or animal trials, and further research, especially clinical trials in humans, is needed to confirm their effectiveness, proper dosage, and long-term safety.